PROGRAM EDUKASI PENCEGAHAN PERILAKU BULLYING ATAU PERUNDUNGAN DI SMP NEGERI 20 PEKANBARU - Ilham Hudi; Dina Alia Zahwa; Nora Maharani; Lexa Angelita; Raja Bulan Devita Aprilia (Jurnal Padamu Negeri, 2026)
This community service activity aimed to enhance students' understanding and awareness regarding bullyingprevention at SMP Negeri 20 Pekanbaru through an educational program. The program was initiated due tothe high prevalence of bullying in school environments, which negatively impacts students' psychological andsocial well-being. The methods employed included preliminary observations, educational material delivery,interactive discussions, and pre-and-post evaluation to measure comprehension levels. Results indicated asignificant improvement in students' ability to identify bullying forms and their consequences, with evaluationscores showing an average increase in awareness of 35%. The involvement of the student council (OSIS) andvisual media played a crucial role in fostering active participation. While cognitive understanding improved,minor verbal interactions outside the classroom still require ongoing monitoring. This activity concludes thatsustainable educational interventions and stakeholder collaboration are vital for a bullying-free schoolenvironment.